INVESTMENT IN RESEARCH AND DEVELOPMENT AS A PREREQUISITE FOR SUSTAINABLE DEVELOPMENT (Heritage, 2023)
In today's world of development, rapid technological changes have shown that only those countries that are able to enter both research and development as well as the development of human resources can hope for sustainable development. The most advanced and economically developed countries of the world base their development on investment in research and development and researchers who are able to create constant innovations. The aim of the work is to show the percentage of investment in research and development in relation to the GDP (gross development product) of the Republic of Serbia in relation to neighboring countries. The relevant data were taken from the Eurostat database, from which a comparison was made over the past five years, taking into account the years in which the Covid-19 pandemic had a significant impact on all socio-economic activities, including investment in research and development. The data show that the Republic of Serbia has a constant increase in investment in research and development and that it reaches 1% of the gross development product, but that is far less than developed countries that invest over 2.5% of the gross national product. In relation to neighboring countries, which are mostly members of the European Union, the Republic of Serbia invests significantly less than Slovenia, but also more than Romania and Bulgaria.
Keywords: research and development, human resources, sustainable development, Republic of Serbia, Eurostat